Bioactivity of an Experimental Dental Implant with Anodized Surface - Maria Fernanda Lima Villaça-Carvalho; Juliani Caroline Ribeiro de Araújo; Juliana Mariano Beraldo; Renata Falchete do Prado; Mari Eli Leonelli de Moraes; Luiz Roberto Coutinho Manhães Junior; Eduardo Norberto Codaro; Heloisa Andrea Acciari; João Paulo Barros Machado; Natal Nerímio Regone; Anderson Oliveira Lobo; Fernanda Roberta Marciano; et al. (Journal of Functional Biomaterials, 2021)
Background: Several studies proved that anodic oxidation improves osseointegration. This study aimed to optimize osseointegration through anodization in dental implants, obtaining anatase phase and controlled nanotopography. Methods: The division of the groups with 60 titanium implants was: control (CG); sandblasted (SG); anodized (AG): anodized pulsed current (duty cycle 30%, 30 V, 0.2 A and 1000 Hz). Before surgery, surface characterization was performed using Atomic Force Microscopy (AFM), Scanning Electron Microscopy (SEM), X-ray Dispersive Energy Spectroscopy (EDS) and Raman Spectroscopy. For in vivo tests, 10 New Zealand white rabbits received an implant from each group. The sacrifice period was 2 and 6 weeks (n = 5) and the specimens were subjected to computed microtomography (μCT) and reverse torque test. Results: AFM and SEM demonstrated a particular nanotopography on the surface in AG; the anatase phase was proved by Raman spectroscopy. In the μCT and in the reverse torque test, the AG group presented better results than the other groups. Conclusion: The chemical composition and structure of the TiO2 film were positively affected by the anodizing technique, intensifying the biological characteristics in osseointegration.